Występowanie porostów naziemnych w wybranych płatach różnych typów siedlisk w okolicach Zalewu Siemianówka w Dolinie Górnej Narwi - Matwiejuk, Anna (Leśne Prace Badawcze, 2016)
This study examines the occurrence of epigeic lichens on study plots located within different types of habitat near the Siemianowka retention reservoir in the Upper Narew Valley. The outcome of this research is a better understanding of epigeic lichens and the problems associated with their distribution and conservation. The investigation of the less common and hence more interesting taxa found within the study area was based on species composition analyses of lichens in different habitats, the degree of recognition in North Eastern Poland and their conservation status as well as threats within the country. A total of 48 lichen species, mainly from the genus of Cladonia, were identified, which is a typical number for these types of habitat. 19% of the species growing on soil are classified as threatened and some of them have been recorded only within this study area. In total, 15 lichen species are under the strict or partial protection.